(3GdeRgQ aj GddZIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCdSf hGddZGJ gPG Yde TQja GHJcQJ JQJjHg GdfhY GdChd ai eYQaI GdUMjM GdKGHJ s
(3BNQgG (B:s
(3hGdgGOi (B: (3GdYfb , hGdCfhGM (B: (3GdcKjQ GdRMjQ ai LQjg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3dZI (B54) s
Keywords: (3GddZIs